Cast in shadow - Sagara, Michelle, 1963- (Sagara, Michelle, 1963- Chronicles of Elantra, 2005)
Kaylin, a Hawk who patrols and polices the City of Elantra, must face her greatest fear when children become the prey of a serial killer, forcing her to return to Nightshade, where she must team up with a powerful Dragon lord she knows she cannot trust.